Twin case of infantile cortical hyperostosis (Caffey disease) with the COL1A1 mutation and literature review in Korea - Shin, Ji Hye; Chang, Mea-Young; Gang, Mi Hyeon; Lim, Han Hyuk (Journal of genetic medicine, 2025)
Infantile cortical hyperostosis, or Caffey disease, is a rare genetic disorder characterized by subperiosteal hyperostosis, primarily affecting the long bones, mandible, clavicle, and ribs. It presents with painful swelling in infancy and typically resolves spontaneously by two years of age. The disease follows an autosomal dominant inheritance pattern and is associated with the c.3040C>T (p.Arg1014Cys) mutation in the COL1A1 gene. We report Korean male twins diagnosed with Caffey disease, both developing painful swelling of the lower extremities before six months of age, with the second twin presenting symptoms two months after the first. Radiographic examinations revealed periosteal hyperostosis in the tibiae, femurs, and upper extremities, with progressive mandibular involvement. Laboratory findings showed elevated serum phosphorus, while other biochemical markers remained normal. Single gene sequencing confirmed the c.3040C>T (p.Arg1014Cys) mutation in the COL1A1 gene, inherited from their asymptomatic mother. Conservative pain management led to gradual symptom resolution, with radiographic improvements observed by 27 months of age. Caffey disease should be considered in infants presenting with acute painful limb swelling, and genetic testing, including parental screening, is crucial for diagnosis. This case provides valuable insights into the familial occurrence, genetic basis, and natural progression of Caffey disease, contributing to a deeper understanding of this rare condition. KCI Citation Count: 0